A Theoretical Study of Correlated Electron in the Frustrated Hubbard Model: Summary Report: Sabbatical Leave Spring 2010 - Enjalran, Matthew (2010)
This sabbatical leave was devoted to conducting theoretical, computational studies of correlated electrons with frustrated interactions and focus on the Hubbard model on the two-dimensional triangular and kagome lattices. Secondly, two Quantum Monte Carlo (QMC) methods were developed and applied to the models of the constrained path/phase QMC, and the determinant QMC methods.
Keywords: dept.phy; faculty_collection; sabbatical_report